An Applied Economic Analysis of Monetary Policy Transmission Channels and Inflation Control in Indonesia - Syamsu Alam; Valentino Aris; Muh Jamil (ARRUS Journal of Social Sciences and Humanities, 2026)
This study analyzes the effectiveness of monetary policy transmission channels in controlling inflation in Indonesia using a Vector Autoregression model. Monthly data from December 2005 to March 2025 include the Federal Funds Rate, Bank Indonesia’s policy rate, inflation, and exchange rate. The results show that Bank Indonesia’s policy rate responds to inflationary pressures within two to four months, while exchange rate movements affect imported inflation within three to seven months. The Federal Funds Rate has fluctuating effects on the exchange rate and inflation, emphasizing the importance of monitoring monetary spillovers. Granger causality results indicate that the BI Rate is the only variable with significant predictive power for the exchange rate at the 5 percent level. Indonesian inflation exhibits strong short term persistence, with shocks remaining the main source of forecast error variance. Over six to ten months, shocks to the BI Rate and Federal Funds Rate jointly explain 20 to 30 percent of inflation variance. FEVD results show that exchange rate pass through is not dominant, although it remains relevant for mitigating imported inflation risks. These findings emphasize the need to accelerate monetary transmission, deepen domestic financial markets, and strengthen coordination between fiscal and monetary authorities to maintain price stability.